Vocabulary learning through traditional and multimedia among intermediate Arabic language learners: CELPAD, IIUM - Abu Bakar, Radhwa; Ismail, Taufik (2015)
ABSTRACT A quasi experimental was conducted by the researcher to explore the effect of traditional and modern method in Arabic vocabulary learning. A total of 62 students form the intermediate level of the Arabic language classes participated in the study. These students were learning the Arabic language as a foreign language. They were assigned into two different groups with 31 students in each group. A set of 30 target words were exposed to both groups via de-contextualization approach. Each group was exposed to a different method of vocabulary learning. Group A was exposed to the traditional method and Group B was exposed to the modern method using multimedia. Each student was required to complete a post-test immediately after the vocabulary learning session. One week later, the students were required to sit for a delayed post-test in order for the researcher to obtain data on vocabulary retention. The result from analyses from the students„ mean scores showed that there were significant differences in the students„ mean scores within the two groups in both immediate and delayed post-test. Through its findings, this paper intends to add to the growing body of knowledge in Arabic language vocabulary acquisition.